Eco-cities: An integrated system dynamics framework and a concise research taxonomy. (September 2015) - Tsolakis, Naoum; Anthopoulos, Leonidas
Highlights: We provide a critical taxonomy for the management of eco-cities. We identify the most critical issues for the design and planning of green cities. We present the development of a SD simulation model of a conceptual eco-city. Our SD model captures the complex nexus of the factors involved in an eco-city. We explore policy interventions for the sustainability performance of eco-cities. Abstract: Urbanism is an emerging phenomenon and international predictions demonstrate that more than half of the increasing world population will live in cities by 2050. Interdisciplinary studies try to develop smart and eco-friendly solutions in order to enhance urban living. This paper validates that the eco-city urban modeling emerges radically and concerns an ideal paradigm for sustainable urban development. After comparing alternative methods for eco-city modeling, this paper attempts to assess the sustainability of the eco-city with the System Dynamics (SD) simulation-based technique. A holistic SD methodological framework is proposed, as a means to assist decision-makers, local governments and managers designing and adopting effective policies for monitoring and assessing the sustainable performance of eco-cities. This framework is formed and tested with two case studies respectively and useful findings about the efficiency of the eco-city modeling are generated.